Can Elastography Differentiate Isolated Fatty Liver from Nonalcoholic Steatohepatitis? - Ajmera, Veeral; Loomba, Rohit (Seminars in Liver Disease, 2018)
Ultrasound and magnetic resonance (MR)-based elastography have demonstrated excellent performance for noninvasive staging of fibrosis in patients with nonalcoholic fatty liver disease (NAFLD); however, their ability to differentiate isolated fatty liver from nonalcoholic steatohepatitis (NASH) is unclear. In this review, the authors provide background on elastography and review the ability of elastography to discriminate between isolated steatosis and NASH. Studies with available data on the diagnosis of NASH histology are limited to vibration-controlled transient elastography and MR elastography. A wide range of optimal cutoffs for the diagnosis of NASH are reported and likely depend on the prevalence of advanced fibrosis in the study population. MR elastography has good performance characteristics for identifying patients with any fibrosis who are at greatest risk of disease-related morbidity. Currently, neither modality can reliably discriminate NASH from simple steatosis. Novel multiparametric MR imaging and elastography are emerging and may help detect presence of NASH in the future.
Keywords: MR elastography; FibroScan; VCTE; nonalcoholic steatohepatitis